PENDIRIAN RUMAH ADAT SUKU NAIBESI SEBAGAI WUJUD PERSEKUTUAN UMAT LINTAS IMAN DAN DAMPAKNYA TERHADAP TOLERANSI ANTARUMAT BERAGAMA DI DESA KUSA - Seran, Yanuarius; Yuliance Uruk, Anita; Benitius Metom, Philipus (JURNAL PROPHETA, 2024)
Culture includes the idea, customs and works of a group of people that are passed down from generation to generation. To imply a cultured person, a place or environment is needed. The environment in question is a traditional house. The establishment of a traditional house is a tradition inherited from the ancestors in society. Suku Naibesi believes that a traditional house is the center of tribal life. The objectives of this study are: to determine the stages of establishing a traditional house, the reasons, meanings, functions, goals and uses of establishing a traditional house, and to determine the relationship between the establishment of a traditional house and the fellowship of interfaith communities and its impact on tolerance between religious communities. The research model used is a descriptive model that explains and predicts the causes and effects of policy choices and obtains data directly related to the culture of the Naibesi Tribe. The research was conducted using a qualitative approach or research based on nature with data sources being community leaders, namely: the Head of the Suku Naibesi, traditional leaders, Muslim and Protestant communities, and communities originating from the feots in the Naibesi Tribe. From the results of the data analysis obtained, the entire Suku Naibesi community believes that the establishment of traditional houses is a form of unity for the entire tribal community.